<span><span>a^<span>x−6</span></span>=<span><span><span>2<span>^x−4</span></span>/4........ hope this answer helps </span></span></span>
Answer:
B) (4x-5i)(4x+5i)
Step-by-step explanation:
The expression can be treated as the difference of squares, and factored accordingly. That factoring is ...
a² -b² = (a -b)(a +b)
__
Here, we have ...
a² -b² = 16x² -(-25)
a² = 16x² ⇒ a = 4x
b² = -25 ⇒ b = √-25 = 5i
Then the factoring is ...
(a -b)(a +b) = (4x -5i)(4x +5i)
Answer:
A
Step-by-step explanation:
Set equation equal to 0
Answer: y=-3
Step-by-step explanation:
Help ASAP only right answers only no spam don’t answer if you don’t know